Neuropharmacological efficacy of metformin for stroke in rodents: A meta-analysis of preclinical trials - Fu, Wenqiao; Tang, Yin; Che, Xudong; Tan, Jiahe; Ma, Yinrui; He, Zhaohui (Frontiers in Pharmacology, 2022)
Background: Stroke, including ischemic stroke, intracerebral hemorrhage, and subarachnoid hemorrhage (SAH), remains a leading cause of mortality globally. Different stroke subtypes have similar detrimental effects in multiple fields of health. Previous research has shown that metformin plays a neuroprotective role in experimental animal models of stroke; however, a preclinical quantitative analysis on the ability of metformin to treat stroke is still lacking. This meta-analysis evaluates the efficacy of metformin in improving stroke prognosis in rodent models of stroke. Methods: Relevant preclinical trials were retrieved from PubMed, EMBASE, and the Web of Science. The neurological score (NS), brain water content (BWC), infarct size, rotarod test, TUNEL, neuron quantity, microglia quantity, and p-AMPK levels were compared between a control group and a metformin group using the standardized mean difference (SMD) and corresponding confidence interval (CI). Quality was assessed with SYRCLE’s risk of bias tool. Results: Fifteen articles published from 2010 to 2022 were included in the meta-analysis. The metformin group had statistically significant differences compared to the control group in the following aspects: NS (SMD −1.45; 95% CI −2.32, −0.58; p = 0.001), BWC (SMD −3.22; 95% CI −4.69, −1.76; p < 0.0001), infarct size (SMD −2.90; 95% CI −3.95, −1.85; p < 0.00001), rotarod test (SMD 2.55; 95% CI 1.87, 3.23; p < 0.00001), TUNEL (SMD -3.63; 95% CI −5.77, −1.48; p = 0.0009), neuron quantity (SMD 3.42; 95% CI 2.51, 4.34; p < 0.00001), microglia quantity (SMD −3.06; 95% CI -4.69, −1.44; p = 0.0002), and p-AMPK levels (SMD 2.92; 95% CI 2.02, 3.82; p < 0.00001). Furthermore, sensitivity analysis and stratified analysis were conducted for heterogeneous outcome indicators. Conclusion: Overall, metformin treatment improves severe outcomes triggered by stroke. Despite the limitations intrinsic to animal studies, this systematic review may provide a vital reference for future high-quality preclinical trials and clinical use.